PENGEMBANGAN MEDIA PUZZLE DIORAMA EKOSISTEM UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN IPAS KELAS III SEKOLAH DASAR - Winda Sri Asih; Titi Anjarini; Muhammad Ferdian Syaifullah (STKIP Subang, 2026)
This study was conducted to address the low level of students’ conceptual understanding of ecosystem materials among third-grade students at SD Negeri Sindurjan. Students experienced difficulties in identifying ecosystem components, understanding food chains, and explaining relationships among living organisms due to the limited use of interactive learning media in classroom instruction. This study aimed to develop an Ecosystem Diorama Puzzle learning media and determine its validity, practicality, and effectiveness in improving students’ conceptual understanding in Science and Social Studies (IPAS) learning, particularly in Chapter III “Living Together with Nature.” The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 18 third-grade students at SD Negeri Sindurjan. Data were collected through observations, interviews, expert validation sheets, response questionnaires, and learning outcome tests. The findings revealed that the developed media achieved validity scores of 95.83% from media experts and 72.91% from material experts, with an average validity score of 84.37%, categorized as very valid. The practicality test resulted in a score of 86.58%, categorized as very practical. Furthermore, the effectiveness test showed a significant improvement in students’ conceptual understanding, indicated by an N-Gain score of 0.74 in the high category. These findings demonstrate that the Ecosystem Diorama Puzzle is a valid, practical, and effective learning media for improving students’ conceptual understanding in elementary school IPAS learning.